Antony Gormley: Reinventing the Classics and Bringing the Body Back to Sculpture - Kochetkova, Ekaterina S. (Actual Problems of Theory and History of Art, 2016)
The article covers some aspects in the art of Antony Gormley, a contemporary British sculptor. The author focuses on the stance that Gormley takes toward the classical tradition of sculpture, on how he follows its line of progress or shifts from it. The main area of study — in the article as well as in most works by Gormley — is the human body and ways of representing it in sculpture. The article defines such crucial qualities of classical sculpture as mass and materiality and reviews how Antony Gormley demonstrates or, on the contrary, denies them. This leads to the conclusion that representation of the body itself is far less important for the artist than his attempt to capture the trace left by that body in space. Accordingly, the very notion of space is very important for Gormley: it is treated both as the void contained within the body, and as the outer environment, with which the sculptures interact. Viewer plays a key part in this interaction: Gormley’s figures are absolutely static and meaningless as they are, and only a living person can create purpose and context for them. Thus, Gormley’s works are communication pieces, as they break the classical distance between a work of art and its audience.